Electro-acoustic tranducers on the basis of thin PZT films - SUROWIAK, Z.; CZEKAJ, D.; BAKIROV, A. A.; DUDKIEVICH, V. P. (Archives of Acoustics, 1999)
In the present work PZT-type thin films have been obtained by RF sputtering and electroacoustic transducers characterized by high sensitivity (γ), wide range of measured relative deformations (η) and high working frequencies (ω) were built. Polycrystalline ferroelectric thin films with the perovskite type structure and chemical composition Pb(Zr0.53Ti0.45W0.01Cd0.01)O3 have been fabricated by RF sputtering. The films exhibited slightly lower values of dielectric constant, residual polarization and piezoelectric coefficient d33 = 80 x 10-12C/N, as compared with the ceramics of the same chemical composition. The thin films keep such a value of d33 up to the Curie point. On the basis of the PZT-type thin films the isotropic and anisotropic piezoelectric sensors were built and investigated. The electrical signal of the isotropic sensors is proportional to the sum of the main components of the relative deformation tensor whereas the signal of the anisotropic sensors depends on the angle φ between the sensor axis and the main axis of the deformation tensor of the sample under investigation. The sensors are characterized by high stability of the generated signal.